What is planetary health? Addressing the environment-health nexus in Southeast Asia in the era of the Sustainable Development Goals: opportunities for International Relations scholars - Paula,Nicole De (2018)
Abstract How can environmental conservation policies integrate concerns for the health and well-being of people whose livelihoods rely directly on nature? How to best operationalize science-policy interfaces to improve evidence-based decision-making? This paper raises policy implications deriving from the poor connectivity between human health and environmental conservation, suggesting the emerging field of “planetary health” as a rich field of research for International Relations scholars.